Faz Game: o jogo digital como ferramenta incentivadora da leitura e da escrita na sala de aula - Gonçalves, Andriele Bairros (2021)
This research aimed to develop a digital game to encourage and promote the construction of knowledge, in the classroom, about the process of teaching and learning reading and writing. In this sense, it was proposed, during the Portuguese language classes, the application of the serious game, created on the Faz Game digital platform. The game had six phases: the first aimed at building knowledge about reading and writing; the second phase addressed the explanation of the textual genre short story; in the third phase, the character of the story was built; in the fourth phase, the scenario of the story was built; in the fifth phase, the first writing of the text was carried out; and, finally, in the sixth phase, the text was rewritten, based on the feedback signaled by the teacher. To support the practice, we used the studies by Fontana and Fialho (2011) on technologies in language teaching; Koch and Elias (2014, 2016) on the conceptions of reading and writing; Alves (2012) and Meira (2019) on digital games; from Vygotsky (2002) on the concept of mediation; by Engeström (2009) on Activity Theory; and Thiollent (2011) on the methodology used in this research. Thus, in this work, we sought, at all times, to mobilize the construction of learning, based on the game created, also emphasizing the importance of the role and mediation that the teacher performs in the classroom, since the game alone cannot handle learning if there is no teacher input. From the results obtained, it is possible to verify that the application of the game was fundamental for the gaps, identified as problematic in this research, to be remedied. In this way, 6th grade students managed not only to understand the importance of reading, but also to develop writing in a cohesive and coherent way. Thus, even though the tool used to create the game has some limitations, which were scored by the students during the assessment, the results achieved are positive, as well as the use of the tool for game development.